Risk of late payment in the Malaysian construction industry - Kho, Mei Ye; Abdul-Rahman, Hamzah (World Academy of Science, Engineering and Technology, 2010)
The purpose of this study is to identify the underlying causes of late payment from the contractors' perspective in the Malaysian construction industry and to recommend effective solutions to mitigate late payment problems. The target groups of respondents in this study were Grades G3, G5, G6 and G7 contractors with specialization in building works and civil engineering works registered with the Construction Industry Development Board (CIDB) in Malaysia. Results from this study were analyzed with Statistical Package for the Social Science (SPSS 15.0). From this study, it was found that respondents have highest ranked five significant variables out of a total of forty-one variables which can caused late payment problems: a) cash flow problems due to deficiencies in client's management capacity (mean = 3.96); b) client's ineffective utilization of funds (mean = 3.88); c) scarcity of capital to finance the project (mean = 3.81); d) clients failure to generate income from bank when sales of houses do not hit the targeted amount (mean=3.72); and e) poor cash flow because of lack of proper process implementation, delay in releasing of the retention monies to contractor and delay in the evaluation and certification of interim and final payment (mean = 3.66).